Возвращение на родину: романы / перевод с английского О. Холмской [и др.] - Харди Томас (1988)
Экземпляры: ЧЗ (20160629) / Инвентарный номер: 27908 / Цена: / Сис.шифр: 84(4/8) / Авт.знак: Г 20 / ГРНТИ: 17 / ББК: 84(4Вел)